Donor–acceptor graphene-based hybrid materials facilitating photo-induced electron-transfer reactions - Stergiou, Anastasios; Pagona, Georgia; Tagmatarchis, Nikos (Beilstein Journal of Nanotechnology, 2014)
Graphene research and in particular the topic of chemical functionalization of graphene has exploded in the last decade. The main aim is to increase the solubility and thereby enhance the processability of the material, which is otherwise insoluble and inapplicable for technological applications when stacked in the form of graphite. To this end, initially, graphite was oxidized under harsh conditions to yield exfoliated graphene oxide sheets that are soluble in aqueous media and amenable to chemical modifications due to the presence of carboxylic acid groups at the edges of the lattice. However, it was obvious that the high-defect framework of graphene oxide cannot be readily utilized in applications that are governed by charge-transfer processes, for example, in solar cells. Alternatively, exfoliated graphene has been applied toward the realization of some donor–acceptor hybrid materials with photo- and/or electro-active components. The main body of research regarding obtaining donor–acceptor hybrid materials based on graphene to facilitate charge-transfer phenomena, which is reviewed here, concerns the incorporation of porphyrins and phthalocyanines onto graphene sheets. Through illustrative schemes, the preparation and most importantly the photophysical properties of such graphene-based ensembles will be described. Important parameters, such as the generation of the charge-separated state upon photoexcitation of the organic electron donor, the lifetimes of the charge-separation and charge-recombination as well as the incident-photon-to-current efficiency value for some donor–acceptor graphene-based hybrids, will be discussed.
Keywords: donor–acceptor; electron-transfer; functionalization; graphene; photophysical properties